2021
DOI: 10.5194/cp-17-951-2021
|View full text |Cite
|
Sign up to set email alerts
|

Tree-ring-based spring precipitation reconstruction in the Sikhote-Alin' Mountain range

Abstract: Abstract. Climate reconstructions provide important insight into past climate variability and help us to understand the large-scale climate drivers and impact of climate change. However, our knowledge about long-term year-to-year climate variability is still limited due to the lack of high-resolution reconstructions. Here, we present the first precipitation reconstructions based on tree rings from Pinus koraiensis (Korean pine) from three sites placed along a latitudinal (330 km) gradient in the Sikhote-Alin' … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…According to forecasts, this trend is expected to continue in the near future [15]. Long-term trends in precipitation change based on meteorological observations and dendrochronological studies have not been found in the region [26]. However, there are trends towards aridification with decreasing elevation and, conversely, towards humidification with increasing elevation [95].…”
Section: Significance Of the Obtained Results From The Perspective Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to forecasts, this trend is expected to continue in the near future [15]. Long-term trends in precipitation change based on meteorological observations and dendrochronological studies have not been found in the region [26]. However, there are trends towards aridification with decreasing elevation and, conversely, towards humidification with increasing elevation [95].…”
Section: Significance Of the Obtained Results From The Perspective Of...mentioning
confidence: 99%
“…Global climate change within the Sikhote-Alin Mountains is manifested by rapid increases in temperatures during the second half of the year and changes in precipitation regime due to processes in the Pacific Ocean. Winter precipitation decreases, while summer precipitation, on the other hand, increases, but the annual total remains almost unchanged [15,25,26]. It has also been observed that there are indirect manifestations of climate change, such as an increase in the number and intensity of tropical cyclones (typhoons) and their northward advancement [6,27].…”
Section: Introductionmentioning
confidence: 99%
“…For the tree‐ring, only width and oxygen isotope (δ 18 O) are used in this study, because tree‐ring density in the study area is believed to indicate the summer temperature change (Duan, 2015). These tree‐ring data are from the World Data Center (WDC) for Paleoclimatology (https://www.ncdc.noaa.gov/data-access/paleoclimatology-data) and recently published papers (Shah et al ., 2007; Xu et al ., 2013; Xu et al ., 2015; Buckley et al ., 2017; Pumijumnong et al ., 2020; Ukhvatkina et al ., 2021). The sample sites are mainly located in the Tibetan Plateau, Mainland Southeast Asia and Japan.…”
Section: Methodsmentioning
confidence: 99%
“…These tree-ring data are from the World Data Center (WDC) for Paleoclimatology (https://www. ncdc.noaa.gov/data-access/paleoclimatology-data) and recently published papers (Shah et al, 2007;Xu et al, 2013;Xu et al, 2015;Buckley et al, 2017;Pumijumnong et al, 2020;Ukhvatkina et al, 2021). The sample sites are mainly located in the Tibetan Plateau, Mainland Southeast Asia and Japan.…”
Section: Proxy Datamentioning
confidence: 99%
“…For the other 32 sites that only have chronologies, EPS is not available thus we use the minimum sample size of 5 to determine the first reliable year. Besides ITRDB, 16 tree-ring chronologies that indicate local precipitation or drought from recently published papers are included in our study (Shah et al, 2007;Sass-Klaassen et al, 2008;Arsalani et al, 2018;Arsalani et al, 2015;Chen et al, 2016;Zhang et al, 2017;Pumijumnong et al, 2020;Xu et al, 2015;Buckley et al, 2017;Ukhvatkina et al, 2021;Akkemik et al, 2020;Kostyakova et al, 2017;Kucherov, 2010). Compared with the tree-ring network used in previous studies over the monsoon Asia region (Cook et al, 2010a;Feng et al, 2013;Shi et al, 2018;Shi et al, 2017), a total of 135 ring-width chronologies are added in our study.…”
Section: Proxy Data Preparingmentioning
confidence: 99%